2005
DOI: 10.1159/000087157
|View full text |Cite
|
Sign up to set email alerts
|

Sonic Motor Pathways in Piranhas with a Reassessment of Phylogenetic Patterns of Sonic Mechanisms among Teleosts

Abstract: Sound production has evolved independently a number of times among teleost fishes. In most cases, sound is generated by fast contracting muscles that vibrate the swim bladder by way of their direct attachment (intrinsic muscles) or indirectly by way of other skeletal elements (extrinsic muscles). This study focuses on the red and black piranha, Pygocentrus nattereri and Serrasalmus rhombeus (superorder Ostariophysi, Order Characiformes), that have extrinsic swim bladder sonic muscles innervated by the third an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
45
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(47 citation statements)
references
References 75 publications
0
45
1
Order By: Relevance
“…Markl (Markl, 1971) and Kastberger (Kastberger, 1981a) found that drumming calls of hand-held specimens consisted of low-frequency harmonic sounds with several pulses and with a period of 7-10ms. These sounds are generated by rapid contractions of sonic muscles, which originate on transverse expansions at the base of the second rib and insert on a broad tendon that ventrally surrounds the cranial sac of the swimbladder (Ladich and Bass, 2005). The sonic muscles are round in shape, extend between the first and third ribs (Ladich and Bass, 2005) and are innervated by branches of the third, fourth and fifth spinal nerves (Onuki et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Markl (Markl, 1971) and Kastberger (Kastberger, 1981a) found that drumming calls of hand-held specimens consisted of low-frequency harmonic sounds with several pulses and with a period of 7-10ms. These sounds are generated by rapid contractions of sonic muscles, which originate on transverse expansions at the base of the second rib and insert on a broad tendon that ventrally surrounds the cranial sac of the swimbladder (Ladich and Bass, 2005). The sonic muscles are round in shape, extend between the first and third ribs (Ladich and Bass, 2005) and are innervated by branches of the third, fourth and fifth spinal nerves (Onuki et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…These sounds are generated by rapid contractions of sonic muscles, which originate on transverse expansions at the base of the second rib and insert on a broad tendon that ventrally surrounds the cranial sac of the swimbladder (Ladich and Bass, 2005). The sonic muscles are round in shape, extend between the first and third ribs (Ladich and Bass, 2005) and are innervated by branches of the third, fourth and fifth spinal nerves (Onuki et al, 2006). Sounds result from fastcontracting sonic muscles, whose contraction rate determines the pulse rate of the drumming sounds (Kastberger, 1981a), which also showed harmonics (Kastberger, 1981b).…”
Section: Introductionmentioning
confidence: 99%
“…Occipital innervation of vocal muscles originating from a VMN at the same hindbrain (rh8)-spinal level is now documented for nine families of closely and distantly related teleost taxa (20,25,55,56) (57).…”
Section: Evolutionary Development Of Sonic-vocal Pattern Generatormentioning
confidence: 99%
“…1A) (24) and pectoral girdle vibration in sculpin that lack a swim bladder (25). Despite these divergent mechanisms, sonic motoneurons are positioned in the same hindbrain-spinal region of the pectoral motor column in sculpin (25,55), catfish (80,81), and gouramis (82). Sonic neurons map to the same location in sea robins, close relatives of sculpin that have sonic muscles completely attached to the swim bladder as in distantly related toadfishes (25).…”
Section: Shared Origins Of Vocal and Pectoral Circuitrymentioning
confidence: 99%
“…1998; Yoshimoto et al, 1999;Carlson and Bass, 2000;Bass and McKibben, 2003;Takayama et al, 2003] indicate that no investigation of the detailed innervation pattern of the sonic muscles of the piranha has been conducted [see also Ladich and Bass, 2005]. Also, studies on the distribution of the sonic motor neurons that innervate the sonic muscles via the spinal nerves are lacking.…”
mentioning
confidence: 99%